Kompetensi tindak direktif anak usia prasekolah - Stiawati, Eti (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
This study aims to assess the competence of preschool children in producing directive acts. The data were collected in the form of utterances containing forms, functions, and strategies of directive acts. The subjects of this study were children aged 3;0–5;0 years from educated families. The theoretical frameworks employed were pragmatic theory and the Ethnography of Communication. The data were analyzed using an interactive model. The results show that preschool children already demonstrate: (1) fourteen competencies of directive acts, (2) six competencies of directive act functions, and (3) strategic competence in performing directive acts both directly and indirectly.